RESEARCH ON THE 8-BALL UNIVERSAL JOINT INNER SLEEVE STRUCTURE AND STATIC STRENGTH DESIGN MATCHING BASED ON STRENGTH FIELD - HUANG JiaWei; LU Xi (Jixie qiangdu, 2021)
In order to design the structure and static strength of the eight-channel constant speed universal joint inner sleeve. In this paper,based on the steel ball selection,the top-down design of structural parameters for the eight channel constant speed universal joint inner sleeve is carried out. The whole field static strength design of internal dangerous section was carried out. We matched the materials and heat treatments of dangerous section with the ideal static strength field. The static strength design was evaluated quantitatively. We carried out the static strength torsion test of constant speed universal joint assembly by using MTS static torsion testing machine,and the inner sleeve was subjected to a micro hardness test to verify the theory. The results show that the eight-channel constant speed universal joint inner sleeve designed according to the static strength design method of structure based on strength field can meet the strength and functional requirements.